Anatolian Iron Ages 7 (Leuven)
x, 332 s.
Keywords: "The seventh international colloquium devoted to the Iron Age of Anatolia and surrounding regions was convened at Edirne, Turkey, between the 19th and 24th April 2010. This volume contains the revised versions of some of the papers delivered at Edirne. They range geographically from southeastern Europe through central and eastern Anatolia to the Trans-Caucasus and northwestern Iran. As a survey of critical issues currently shaping discourse on Iron Age Anatolia, they provide an invaluable body of new information and ideas." --